Studies on environmental resistomes in polychaete gut microbiome from polluted estuaries - Ganesan, Mirunalini; Mani, Ravi; Saikumar, Sakthinarenderan; Chang, Soon Woong; Ravi, Karthikeyan; Mani, Ravishankar Ram; Ravindran, Balasubramani (Frontiers in Marine Science, 2025)
IntroductionAntimicrobial resistance (AMR) is a growing public health concern, and understanding the processes driving its growth is crucial.MethodologyThe study investigates the link between heavy metal/biocide (BMRGs) and antibiotic resistance genes (ARGs) and the presence of mobile genetic elements (MGEs) in the polychaete gut microbiome from four differently polluted estuaries along the Southeast coast of India- Adyar Estuary (S1), Ennore Creek (S2), Penna Sangamam (S3), and Pazhayakayal Estuary (S4), using whole metagenome sequencing.ResultsICPOES analysis for the tissue, sediment and water revealed the presence of high concentration of Zn, Fe, and Cu in sediment and tissue and high levels of Hg and Zn in water and bioaccumulation of Cu and Fe in polychaete tissues, especially in S2 and S4. A total of 2054 ARGs has been identified in all four samples and mostly belonging to class of Cephalosporin and Carbapenem. MRGs against Cu, Fe and Zn were predominantly found in all four samples. MGEs were extensively present in S4 & S2. The co-occurrence analysis of ARGs, BMRGs & MGEs revealed the presence of high co-occurrence in S2 & S4 samples. Risk score assessment indicated that the S2 and S4 samples have a high potential for spreading AMR across ecosystems.DiscussionThe findings suggest that industrial effluents discharged into rivers and aquatic ecosystems and presence of heavy metals beyond permissible limit could contribute to the spread of AMR through the co-selection of BMRGs.